Perancangan Bisnis Model Bank Sampah Bersinar Menggunakan Circular Business Model Canvas dengan Penerapan Circular Economy - Raden Dieva Qinthara; Endang Chumaidiyah; Agus Achmad Suhendra (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Bank Sampah Bersinar or BSB is the largest waste bank managed by PT. Solusi Rahayu Indonesia is located in West Java Province located on Jalan Terusan Bojongsoang No 174A, Bandung Regency - West Java in 2014 in the background by environmental conditions and the community around the banks of the Citarum River. Since 2019, the Waste Bank has opened services for the community related to waste management. There are several obstacles experienced such as the reduction of managed waste as seen from the number of Unit Waste Banks, the value of the circular economy, and the number of Shining Waste Bank partners which each decreased. Looking at these three aspects, it shows that the Bersinar Waste Bank has experienced a decline in operational performance. This research uses the Circular Business Model Canvas (CBMC) approach, SWOT Analysis, Business Model Environment, ReSOLVE Framework, and Fitting Value Map to help improve the performance of the Bersinar Waste Bank in processing waste so that the income obtained can also increase. The data collection of this research was obtained from the results of interviews with customers to find out the customer profile and business model environment, analyze 9 existing business model canvas blocks with the ReSOLVE Framework and distribute questionnaires to find out SWOT to experts in the field of waste management. Based on the calculation of strategy analysis and positioning map with SWOT shows that the Shining Waste Bank is in quadrant II, indicating that the company is in a strong position but must be able to face a great threat. The Circular Business Model Canvas is one way to implement the circular economy for companies through an analytical model. In the framework of the Circular Business Model Canvas, it is carried out by adding proposals to several blocks such as customer segments, value propositions, channels, customer relationships, revenue streams, and key activities as well as adding blocks, namely take-back systems and adoption factors as a form of adaptation of the business model transition to a circular economy.